Feeding, artificial sucking habits, and malocclusions in 3-year-old girls in different regions of the world - (:unkn) unknown (My University, 2005)
Purpose: The way babies and young children are reared is important to their health and development. Extensive breast-feeding has also been shown to reduce the development of artificial sucking habits like digit or pacifier-sucking. The aim of this study was to determine feeding methods, artificial sucking habits, and the presence of malocclusions in 3-year-old girls living in different regions of the world. Methods: Children from the following countries were involved in the present study: (1) Brazil (Porto Alegre); (2) Japan (Niigata); (3) Mexico (Mexico City); (4) Norway (Oslo); (5) Sweden (Falköping); (6) Turkey (Istanbul); (7) and the United States (Iowa City, Iowa). During the interview and examination, the following variables were evaluated and registered: (1) breast-feeding and bottle-feeding; (2) duration and frequency; (3) sucking habits; (4) posterior and anterior crossbites; and (5) other malocclusions/normal occlusion. Results: The prevalence of breast-feeding was very high in all groups, ranging between 78% and 98%. The prevalence of bottle-feeding in the different areas was also high. Except for Iowa City, the prevalence of digit-sucking was relatively low. Pacifier-sucking is fairly popular in most areas, with the exception of Niigata. The prevalence of normal occlusion in different cities ranged from 38% to 98%. Conclusions: There are considerable differences in feeding, as well as artificial sucking habits, in different areas of the world and at different periods.
Keywords: Feeding; Finger-sucking; Malocclusion; Pacifier